Inhibition of post-surgery tumour recurrence via a sprayable chemo-immunotherapy gel releasing PD-L1 antibody and platelet-derived small EVs - Jian Zhao; Hao Ye; Qi Lu; Kaiyuan Wang; Xiaofeng Chen; Jiaxuan Song; Helin Wang; Yutong Lu; Maosheng Cheng; Zhonggui He; Yinglei Zhai; Haotian Zhang; et al. (Journal of Nanobiotechnology, 2022)
Abstract Background Melanoma is the most serious type of skin cancer, and surgery is an effective method to treat melanoma. Unfortunately, local residual micro-infiltrated tumour cells and systemic circulating tumour cells (CTCs) are significant causes of treatment failure, leading to tumour recurrence and metastasis. Methods Small EVs were isolated from platelets by differential centrifugation, and doxorubicin-loaded small EVs (PexD) was prepared by mixing small EVs with doxorubicin (DOX). PexD and an anti-PD-L1 monoclonal antibody (aPD-L1) were co-encapsulated in fibrin gel. The synergistic antitumour efficacy of the gel containing PexD and aPD-L1 was assessed both in vitro and in vivo. Results Herein, we developed an in situ-formed bioresponsive gel combined with chemoimmunotherapeutic agents as a drug reservoir that could effectively inhibit both local tumour recurrence and tumour metastasis. In comparison with a DOX solution, PexD could better bind to tumour cells, induce more tumour immunogenic cell death (ICD) and promote a stronger antitumour immune response. PexD could enter the blood circulation through damaged blood vessels to track and eliminate CTCs. The concurrent release of aPD-L1 at the tumour site could impair the PD-1/PD-L1 pathway and restore the tumour-killing effect of cytotoxic T cells. This chemoimmunotherapeutic strategy triggered relatively strong T cell immune responses, significantly improving the tumour immune microenvironment. Conclusion Our findings indicated that the immunotherapeutic fibrin gel could “awaken” the host innate immune system to inhibit both local tumour recurrence post-surgery and metastatic potential, thus, it could serve as a promising approach to prevent tumour recurrence. Graphical Abstract